Testing a model of antecedents and consequences of defensive pessimism and self-handicapping in school physical education - Ntoumanis, Nikos; Taylor, I.; Standage, M. (Routledge, 2010)
There has been very limited research on the use of self-worth protection strategies in the achievement context of school physical education (PE). Thus the aim of the present study was to examine some antecedents and consequences of defensive pessimism and self-handicapping. The sample comprised 534 British pupils (275 females, 259 males) recruited from two schools who responded to established questionnaires. Results of structural equation modelling analysis indicated that selfhandicapping and defensive pessimism were positively predicted by fear of failure and negatively predicted by competence valuation. In addition, defensive pessimism was negatively predicted by physical self-concept. In turn, defensive pessimism negatively predicted enjoyment in PE and intentions to participate in future optional PE programmes. Self-handicapping did not predict enjoyment or intentions. Results from multi-sample structural equation modelling showed the specified model to be largely invariant across males and females. The findings indicate that although both strategies aim to protect one's selfworth, some of their antecedents and consequences in PE may differ. © 2010 Taylor & Francis.